An Integrated Proteomics and Bioinformatics Analysis of the Anticancer Properties of RT2 Antimicrobial Peptide on Human Colon Cancer (Caco-2) Cells - Surachai Maijaroen; Sompong Klaynongsruang; Sittiruk Roytrakul; Monruedee Konkchaiyaphum; Lapatrada Taemaitree; Nisachon Jangpromma (Molecules, 2022)
New selective, efficacious chemotherapy agents are in demand as traditional drugs display side effects and face growing resistance upon continued administration. To this end, bioactive molecules such as peptides are attracting interest. RT2 is a cationic peptide that was used as an antimicrobial but is being repurposed for targeting cancer. In this work, we investigate the mechanism by which this peptide targets Caco-2 human colon cancer cells, one of the most prevalent and metastatic cancers. Combining label-free proteomics with bioinformatics data, our data explore over 1000 proteins to identify 133 proteins that are downregulated and 79 proteins that are upregulated upon treatment with RT2. These changes occur in a dose-dependent manner and suggest the former group are related to anticancer cell proliferation; the latter group is closely related to apoptosis levels. The mRNA levels of several genes (FGF8, PAPSS2, CDK12, LDHA, PRKCSH, CSE1L, STARD13, TLE3, and OGDHL) were quantified using RT-qPCR and were found to be in agreement with proteomic results. Collectively, the global change in Caco-2 cell protein abundance suggests that RT2 triggers multiple mechanisms, including cell proliferation reduction, apoptosis activation, and alteration of cancerous cell metabolism.